Asymmetric Spillover Effects Between Agricultural Commodity Prices and Biofuel Energy Prices - Apergis, Nicholas; Eleftheriou, Sofia; Voliotis, Dimitrios (International Journal of Energy Economics and Policy, 2017)
This study addresses the problem of causal price relationships of biofuels for an enhanced group of agricultural commodities to capture possible asymmetric causal effects. It investigates the long-run equilibrium and assumes that an adjustment process toward this equilibrium exists. The adjustment process can be non-linear, implying that we can identify critical thresholds that determine regions in the sample that once exceeded, price inter linkages may vary. The empirical results indicate that there are commodity prices that have strong causal (asymmetric) relationship with biofuel energy prices. Keywords: Biofuels energy prices; agricultural prices; asymmetric cointegration; asymmetric causality JEL Classification: Q16